Immunobiologics in juvenile dermatomyositis: a systematic review of promising therapeutic advances - Aline Maria de Oliveira Rocha; Gabriel Fidelis Ribeiro; Juliana Capecce Silva (Rheumatology)
Introduction To identify the most effective treatment for juvenile dermatomyositis (JDM), considering efficacy, safety, impact on patients and improvement in their quality of life.